Pengaruh Terapi Aktivitas Kelompok Stimulasi Persepsi terhadap Kemampuan Mengontrol Marah pada Klien Resiko Perilaku Kekerasan di Rumah Sakit Grhasia Propinsi DIY - Hasanah, Uswatun (STIKES 'Aisyiyah Yogyakarta, 2008)
Background: The problem that emerges will precipitate depress of human psyche, and it requires the human to solve them so that the balancing of their psyche can be defended. If the condition that makes depress of psyche can’t solved with well-coping mechanism, so the impaired psyche will increased, and experiences impaired health psychiatrics. Impaired psyche that more occurs is risk violence behavior that is begun from inability to control of angry. The purpose: it is to know about the influence stimulation perception of group activity therapy toward ability to control angry to client that risked for violence behavior in GRHASIA Hospital of special province of Yogyakarta. Method: True experiment research with plan of research is pretest-posttest with control group. In this plan, the group is conducted randomization. The population is client that is risked of violence behavior that is hospitalized in GRHASIA Hospital of special province of Yogyakarta 2008 with sample 13th respondent that is fulfill inclusion criteria. The technique of sampling is cluster sampling. The collect of data to ability of control angry used questioner and observation checklist. The analysis relationship of two variables is used t-test statistics test with signification p<0, 05. Result: In the experiment group that is gotten that before is given group activity therapy, they have ability to control emotion that is enough, exactly after they are given group activity therapy, the number that is have ability to control angry is increase theirs state become they have well-ability to control angry. In the control group, it is gotten that while pretest and posttest nothing any changes, the subject have ability to control angry that enough. The group activity therapy that is given by researcher is proved